2004
DOI: 10.1002/art.20286
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microsomal prostaglandin E synthase 1 in rheumatoid arthritis synovium

Abstract: Objective. Microsomal prostaglandin E synthase 1 (mPGES-1) catalyzes the formation of PGE 2 from cyclooxygenase-derived PGH 2 . Microsomal PGES-1 is induced by proinflammatory cytokines and is strongly linked to conditions that result in high PGE 2 biosynthesis. PGE 2 contributes to the pathogenesis of rheumatoid arthritis (RA), acting as a mediator of inflammation and promoting bone destruction. Induction of mPGES-1 in rheumatoid synoviocytes by proinflammatory cytokines has been demonstrated in vitro, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 16 publications
(22 reference statements)
6
103
0
4
Order By: Relevance
“…zileuton) and studies on 5-LOX-or 5-LOXactivating protein-deficient mice, exclude a prominent role of LTs in OA or RA (Werz and Steinhilber, 2006). However, PGE2 is a key mediator accounting for typical disease symptoms in OA and RA (Smith, 1989); and in patients suffering from RA or OA, a pivotal role for mPGES1 has been demonstrated (Westman et al, 2004;Li et al, 2005). Moreover, data from animal arthritis models support the relevance of mPGES1 to inflammatory joint diseases (Claveau et al, 2003;Trebino et al, 2003;Guay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…zileuton) and studies on 5-LOX-or 5-LOXactivating protein-deficient mice, exclude a prominent role of LTs in OA or RA (Werz and Steinhilber, 2006). However, PGE2 is a key mediator accounting for typical disease symptoms in OA and RA (Smith, 1989); and in patients suffering from RA or OA, a pivotal role for mPGES1 has been demonstrated (Westman et al, 2004;Li et al, 2005). Moreover, data from animal arthritis models support the relevance of mPGES1 to inflammatory joint diseases (Claveau et al, 2003;Trebino et al, 2003;Guay et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Double immunofluorescence staining was performed using mouse monoclonal anti-HLA-DR (BD Biosciences) and rabbit polyclonal anti-5-HT2A antibodies (Sigma Chemicals) as published previously. 29 …”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…Previous studies demonstrated that IL-1b markedly increased mPGES-1 mRNA and protein expression, in parallel with an increase in PGE 2 levels in chondrocytes (9,10). Interestingly, accumulating evidences involve mPGES-1 in cartilage degradation (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 97%